2017
DOI: 10.1177/0047239517749245
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Graduate Student Writers With VoiceThread

Abstract: This qualitative case study examined the influence of the use of VoiceThread technology on the feedback process for thesis writing in two online asynchronous graduate courses. The influence on instructor feedback process and graduate student writers’ perceptions of the use of VoiceThread were the foci of the study. Master’s-level students ( n = 18) in two different degree programs received and responded to multiple rounds of instructor feedback on their thesis paper via VoiceThread technology for one semester.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Creation of Video-Based Feedback Mathisen (2012) reported that the process of creating video-based feedback was intuitive for instructors. Many studies reported that providing video-based feedback, required less time than providing written feedback (Denton, 2014;Gonzalez & Moore, 2018;Griffiths & Graham, 2010;Henderson & Phillips, 2015;Lamey, 2015;Mathisen, 2012) or the same amount of time (Crook et al, 2012;Jones et al, 2012;O'Malley, 2011;Schilling & Estell, 2014;Vincelette & Bostic, 2013;West & Turner, 2016). Gonzalez & Moore (2018) found that relying solely on video feedback reduced time spent on each submission compared to written comments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Creation of Video-Based Feedback Mathisen (2012) reported that the process of creating video-based feedback was intuitive for instructors. Many studies reported that providing video-based feedback, required less time than providing written feedback (Denton, 2014;Gonzalez & Moore, 2018;Griffiths & Graham, 2010;Henderson & Phillips, 2015;Lamey, 2015;Mathisen, 2012) or the same amount of time (Crook et al, 2012;Jones et al, 2012;O'Malley, 2011;Schilling & Estell, 2014;Vincelette & Bostic, 2013;West & Turner, 2016). Gonzalez & Moore (2018) found that relying solely on video feedback reduced time spent on each submission compared to written comments.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies reported that providing video-based feedback, required less time than providing written feedback (Denton, 2014;Gonzalez & Moore, 2018;Griffiths & Graham, 2010;Henderson & Phillips, 2015;Lamey, 2015;Mathisen, 2012) or the same amount of time (Crook et al, 2012;Jones et al, 2012;O'Malley, 2011;Schilling & Estell, 2014;Vincelette & Bostic, 2013;West & Turner, 2016). Gonzalez & Moore (2018) found that relying solely on video feedback reduced time spent on each submission compared to written comments. Henderson & Phillips (2015) reported that creating videos took, on average, half the amount of time as annotating submissions.…”
Section: Resultsmentioning
confidence: 99%
“…That audio feedback is a more personal experience is consistently highlighted with students reporting that audio comments are more intimate and individualised than written feedback, which is often seen as formal and impersonal (Carruthers et al, 2015;Chew, 2014;Gonzalez & Moore, 2018;Hennessy & Forrester, 2014;Knauf, 2016;McCarthy, 2015). This is attributed to the fact that tone of voice lends a more engaging 'human' quality to the feedback (Chew, 2014).…”
Section: The Student Experience Of Audio Feedbackmentioning
confidence: 99%
“…This is attributed to the fact that tone of voice lends a more engaging 'human' quality to the feedback (Chew, 2014). Hearing the tutor's voice can create feelings of proximity (Gonzalez & Moore, 2018;Lunt & Curran, 2010;Munro & Hollingworth, 2014) and convey a more caring attitude on the part of the tutor (Ice et al, 2007). Students also report that audio feedback indicates more appreciation of their work by tutors (Chew, 2014;Gonzalez & Moore, 2018;Hennessy & Forrester, 2014;Knauf, 2016).…”
Section: The Student Experience Of Audio Feedbackmentioning
confidence: 99%
“…Moreover, each assignment's due dates must be determined within a longer time frame to allow for multiple due dates in order to give students time for feedback (see Appendices I & J). This planning follows Gonzalez & Moore's (2017) assertion that "effective instructor feedback should explicitly state expectations for improvement and adhere to agreed upon timelines (i.e., when feedback will be sent to student) between the students and the instructor" (p. 3). The solution to this might be simply to adjust to the number of 'Rs' needed given contextual constraints or to set up a 'rhythm' for VoiceThread assignments such as " [e]very Monday you record, every Tuesday you give feedback, you revise until Friday when you teacher will grade your assignment."…”
Section: Caveatsmentioning
confidence: 99%